2021
DOI: 10.1039/d1gc00226k
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-flow electro-oxidative coupling of sulfides with activated methylene compounds leading to sulfur ylides

Abstract: An unprecedentedly straightforward electro-oxidative coupling of sulfide with activated methylene compound to synthesize sulfur ylide has been developed. Good to excellent yields can be obtained under catalyst- and oxidant-free conditions...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…Moreover, a slight lower oxidation peak of 3 (1.47 V, black, Figure b) than that of BHT was observed. The results above revealed that the inclusion of a radical scavenger did not inhibit the oxidation of catalysts and reactants and provided strong support for the existence of radical process . No obvious inhibition on reaction efficiency was observed in the presence of DABCO or in the dark, which ruled out the involvement of photosensitized singlet oxygenation (Scheme c).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Moreover, a slight lower oxidation peak of 3 (1.47 V, black, Figure b) than that of BHT was observed. The results above revealed that the inclusion of a radical scavenger did not inhibit the oxidation of catalysts and reactants and provided strong support for the existence of radical process . No obvious inhibition on reaction efficiency was observed in the presence of DABCO or in the dark, which ruled out the involvement of photosensitized singlet oxygenation (Scheme c).…”
Section: Resultsmentioning
confidence: 73%
“…The results above revealed that the inclusion of a radical scavenger did not inhibit the oxidation of catalysts and reactants and provided strong support for the existence of radical process. 82 No obvious inhibition on reaction efficiency was observed in the presence of DABCO or in the dark, which ruled out the involvement of photosensitized singlet oxygenation 83 (Scheme 3c). Good yield was obtained when the reaction was conducted in the presence of superoxide radical anion (O 2…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…We also succeeded in converting a sterically congested tetrasubstituted alkene to cyclopropyl ketone 51 . Note that this electrocatalytic system is not applicable to intermolecular cyclopropanation, likely because of competitive direct coupling of the phenothiazine catalyst with the active methylene compounds to form sulfur ylides …”
Section: Resultsmentioning
confidence: 99%
“…Ylides derived from functionalization of the sulfur of aryl phenothiazines have previously been reported. 25 Further attempted transformations by quenching with an electrophile other than a proton revealed this could not readily be turned into a three-component coupling. Attempting to quench the presumed organomagnesium intermediate formed after addition of the phenothiazide to the benzyne with either diphenylchlorophosphine 5a or Weinreb amide 5b did not result in productive formation of compounds 6a or 6b (Equation 2, Scheme 3).…”
Section: Scheme 3 Limitations In Scopementioning
confidence: 99%